GEOMETRIC MODEL OF THE NAZCA PLATE SUBDUCTION IN SOUTHWEST COLOMBIA - Monsalve J Hugo; Pedraza Garcia Patricia; Vargas Carlos Alberto (Earth Sciences Research Journal)
A geometric model for the subduction of the Nazca plate beneath the South American plate in southwestern of Colombia is proposed based on the relocation of hypocenters of local and distant earthquakes. By means of the simultaneous inversion of teleseismic P and SH body waves, the depths of the 15 events with Mw ≥ 5.8 were constrained, and the hypocenters of the 250 earthquakes recorded between 1990 and 2005 by the International Seismological Centre (ISC) and U.S. Geological Survey, National Earthquake Information Center (NEIC) were constrained and relocated. A model is proposed for the hypocentral sections taking into account the trench along of the Earth and Colombia-Ecuador. Three different possible shapes of subduction of the Nazca plate in the Colombia-Ecuador trench were obtained: The first configuration, in the Cali A segment, the dip angle changes from17º to 45º down to a maximum depth of 100km; the second configuration, in the Popayán B and Nariño C segments, the dip angle holds approximately constant at 30º down to a maximum depth of 200 km; and the third configuration, in the Quito D segment, the dip angle changes of 9º to 50º to a maximum depth 220 km. The maximum depth of seismicity along the Colombia-Ecuador trench shows two increases, the first between latitudes 4.5ºN-5ºN and the second between the latitudes 1ºS-2ºS, which suggest that the presence of the Malpelo and Carnegie Ridges may generate a differential blockage at the Pacific Colombia-Ecuador basin.